The Collision between Freedom of Expression and Human Dignity in the Jurisprudence of the Hungarian Constitutional Court : The Protection of Public Speech from Public Figures to Public Affairs - Tóth, J. Zoltán (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Freedom of expression – among the classical freedom rights – became an integral part of European legal culture in the 16th century, in parallel with the emergence of Protestant denominations. The definition of the limits to freedom of expression within the framework of the rule of law has been a topical issue of jurisprudence and legal theory ever since. The aim of this paper is to briefly review the process by which the Constitutional Court has gradually shifted in recent years from the enforcement of subjective criteria to the assessment of substantive ones in the context of the examination of freedom of expression in the public sphere – especially in criminal cases, in relation to the constitutional assessment of defamation and libel – is no longer the question of who the opinion (or the press release) is about (e.g. public figures), but rather on the type of matter (i.e. public or non-public) in which it appears. Of course, the being of public figures is still a possible aspect of the assessment, but it can now be carried out primarily (and subordinately) in order to determine whether the facts under constitutional assessment are indeed public matters (and thus whether the „speech” made in this context is covered by the special protection of freedom of expression in political and social matters) or not.